(untitled) (Indonesian Theological Justice Review, 2025)
In Indonesia, religious leaders hold significant influence over both their followers and broader societal norms. This paper explores the role of religious leaders in shaping political justice, focusing on their contributions to public policy and social issues. By examining the involvement of Islamic, Christian, and other religious leaders in Indonesia’s political landscape, the study assesses how they advocate for policies related to social justice, human rights, and economic equity. Drawing from case studies of religious leaders’ activism during key political events—such as advocating for democracy post-1998, opposing corruption, or promoting environmental justice—the paper identifies the ethical and moral frameworks religious leaders use to engage in public policy debates. The paper argues that religious leaders in Indonesia can play a transformative role in advocating for policies that promote justice and equity, using their moral authority to influence both local and national government decisions. However, the study also highlights challenges, such as political polarization, religious intolerance, and the tension between religious dogma and secular governance. Recommendations include fostering greater political engagement among religious leaders, creating platforms for interfaith dialogue on public policy, and encouraging religious leaders to take stronger stances on issues of social justice.